New insights from mercury isotopes of a No.3 coal in Tengnan Coalfield, Shandong Province, Eastern China: With emphasis on source of harmful trace elements - Mengqi Du; Wenwu Zhao; Mingxiao Sun; Balaji Panchal; Cunliang Zhao (Energy Exploration & Exploitation)
Mercury (Hg) is a critical pollutant in coal deposits, yet its sources and enrichment mechanisms remain debated. Mercury concentrations detected in ancient sedimentary deposits have frequently been employed as an indicator of volcanic activity, notably those associated with eruptions from large igneous provinces. Yet, this correlation requires careful evaluation, as multiple Hg sources may contribute to its enrichment in sedimentary environments. Potential Hg sources include volcanic emissions, hydrothermal fluids, anthropogenic activities, and other geogenic inputs. The examination of mass-dependent fractionation and mass-independent fractionation in laboratory experiments has increased the feasibility of employing mercury isotopic methodologies to deduce the origins of deleterious trace elements in environmental systems. The harmful trace elements Be, F, V, Cr, Cu, As, Se, Mo, Tl, Pb, U, and Hg show abnormal enrichment in the stratigraphic samples JY-3-1 and JY-3-9 from the Tengnan Coalfield. In the low-temperature hydrothermally altered coal seams of the Jinyuan Mine in southwestern Shandong Province, sulfide and clay minerals are likely the main carriers of mercury. This study aims to indirectly infer the sources of other harmful trace elements strongly correlated with mercury enrichment. A nuanced interpretation of Hg isotope data is necessary due to the complexity of multiple-source mixing, post-depositional modifications, and isotopic fractionation processes. Through the integration of mercury isotope analysis with a suite of analytical techniques, including geochemical analysis, mineralogical studies, and geological surveys, the results indicate that the sources of harmful trace elements in the No. 3 coal of the Jinyuan Mine are predominantly influenced by volcanic activity, atmospheric precipitation, and terrigenous sediment input, with a minor contribution from coal-forming plants. The application of Hg isotopes allows for more effective regulation of high-Hg coal usage, enabling policymakers to implement stricter emission controls, promote cleaner coal technologies, and establish Hg-specific air quality standards.